Conflict, Mediated Message, and Group Dynamics: Intersections of Communication - Croucher, Stephen M.; Lewandowska-Tomaszczyk, Barbara; Wilson, Paul A. (Lexington Books, 2017)
Conflict, Mediated Message, and Group Dynamics: Intersections of Communication establishes up a framework to explore the ways in which emotions enter a conflict scenario and investigate their role either as causes or consequences of conflict. The volume's chapters shed new light on the questions of the extent to which context on the one hand and culture-related dimensions on the other are conducive to conflict dynamicity and management either by calming emotions—and conflict—or by increasing their severity.